THERAPY FOR LOW BACK PAIN WITH ACUPUNCTURE AND TURMERIC - Aszar, Farah Dynah Daeq; Imandiri, Ario; Mustika, Arifa (Journal of Vocational Health Studies, 2018)
Background: Low Back pain (LBP) is the most common musculoskeletal disorder, affecting 70% - 85% of the adult population, and twelve months after onset of LBP, 45% - 75% of patients are still sick. Low back pain in Traditional Chinese Medicine (TCM) is usually associated with kidney or renal meridians. In She syndrome, lower back pain is often caused by pathogen wind, damp, cold, heat and blood stasis, whereas in the Xi syndrome lower back pain usually caused by deficiency of Jing, Qi, Yin, or Yang of the  kidney. Purpose: To know the effect of acupuncture therapy at Pishu (BL 20), Shenshu (BL 23), Dachangshu (BL 25), Waiguan (TE 5) as well as herbal therapy  using turmeric (Curcuma domestica) on low back pain sufferers. Method: Acupuncture therapy at Pishu (BL 20), Shenshu (BL 23), Dachangshu (BL 25), Waiguan (TE 5) were given 12 times, 3 times a week. Herbal therapy was given for 30 days, taken 3 times a day with a dose of turmeric 1 gram. Result: This therapy could reduce the scale of low back pain from scale 8 to 0 and the spasme scale from 3 to 0, that also reducing the frequency of low back pain. Conclusion: Acupuncture therapy at Pishu (BL 20), Shenshu (BL 23), Dachangshu (BL 25), Waiguan (TE 5) and herbal therapy with 3 g of turmeric (Curcuma domestica) could resolve lower back pain.